Major Groove Interactions of Vaccinia Topo I Provide Specificity by Optimally Positioning the Covalent Phosphotyrosine Linkage - Nagarajan, Rajesh (2006)
Vaccinia DNA topoisomerase (vTopo) is a prototypic eukaryotic type I topoisomerase that shows high specificity for nucleophilic substitution at a single phosphodiester linkage in the pentapyrimidine recognition sequence 5′-(C/T)(+5)C(+4)C(+3)T(+2)T(+1)p↓N(-1). This reaction involves reversible transesterification where the active site tyrosine of the enzyme and a 5′ hydroxyl nucleophile of DNA compete for attack at the phosphoryl group. The finite lifetime of the covalent phosphotyrosine adduct allows the enzyme to relax multiple supercoils by rotation of the 5′ OH strand before the DNA backbone is religated. To dissect the nature of the unique sequence specificity, subtle modifications to the major groove of the GGGAA-5′ sequence of the non-scissile strand were introduced and their effects on each step of the catalytic cycle were measured. Although these modifications had no effect on noncovalent DNA binding (K(D)), or the rate of reversible DNA cleavage (k(cl)), significant decreases in the cleavage equilibrium (K(cl) = k(cl)/k(r)) were observed arising from increased rates of 5′ hydroxyl attack (kr) at the phosphotyrosine linkage. These data and other findings support a model where major groove interactions are used to position the phosphotyrosine linkage relative to the mobile 5′ hydroxyl nucleophile. In the absence of native sequence interactions, the phosphotyrosine has a higher probability of encountering the 5′ hydroxyl nucleophile leading to an enhanced rate of ligation and a diminished equilibrium constant for cleavage. By this unusual specificity mechanism the enzyme prevents formation of stable covalent adducts at nonconsensus sites in genomic DNA.